2006
DOI: 10.1302/0301-620x.88b9.17708
|View full text |Cite
|
Sign up to set email alerts
|

Homologous blood transfusion is not required in surgery for adolescent idiopathic scoliosis

Abstract: We studied 70 consecutive patients with adolescent idiopathic scoliosis who underwent corrective surgery. They were divided into two groups. In the study group of 38 patients one or more modern blood-conservation measures was used peri-operatively. The 32 patients in the control group did not have these measures. Both groups were similar in regard to age, body-weight, the number of levels fused and the type of surgery. Only two patients in the study group were transfused with homologous blood and these transfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 33 publications
0
16
1
3
Order By: Relevance
“…Routine use of blood conservation measures can decrease the need for allogeneic blood transfusion [18]. These techniques are varied and include intraoperative controlled hypotension (directly reducing the volume of blood lost) and acute normovolaemic haemodilution which reduces the proportion of red cells lost intraoperatively [18,31,32].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Routine use of blood conservation measures can decrease the need for allogeneic blood transfusion [18]. These techniques are varied and include intraoperative controlled hypotension (directly reducing the volume of blood lost) and acute normovolaemic haemodilution which reduces the proportion of red cells lost intraoperatively [18,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…These techniques are varied and include intraoperative controlled hypotension (directly reducing the volume of blood lost) and acute normovolaemic haemodilution which reduces the proportion of red cells lost intraoperatively [18,31,32]. Infusion of antifibrinolytic drugs such as tranexamic acid can also decrease the need for allogeneic blood transfusion by competitive inhibition of the activation of plasminogen to plasmin [22,33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…72 Studies have shown that a combined approach to blood conservation makes it possible to avoid allogenic blood transfusions. 45,53,73,74 However, until their efficacy and adverse effects are resolved through further trials, clinicians must weigh the cost and consequences of hemostatic medications and blood conservation techniques against the risk of substantial perioperative blood loss and of allogenic blood transfusions. 75 …”
Section: Other Agentsmentioning
confidence: 99%